Consecutive Purple Sweet Potato Vinegar Fermentation Using Mixed Starter of Aspergillus spp, Saccharomyces Cerevisiae, and Dried Starter of Acetobacter pasteurianus - Cakrawati, Dewi; Hongsprabhas, P. (ASEAN Journal of Science and Engineering, 2024)
This study investigated the effect of sorbent material on the viability of dried A. pasteurianus starter and the use of defined starter culture of fungi Aspergillus spp, yeast S. cerevisiae, and dried A. pasteurianus starter during purple sweet potato vinegar fermentation.  Complex carbohydrate in cultivation media protects cells during drying, while rice flour as sorbent material absorbs water to obtain dried starter of A. pasteurianus. Increasing the ratio of cultivation media and sorbent material from 1:1 to 1:2 could reduce aw of dried A. pasteurianus starter that will prolong storage time. Mixed starter of Aspergillus spp, yeast S. cerevisiae, and dried A. pasteurianus starter could convert starch to glucose to EtOH to acetic acid during fermentation. However, media saccharified by A. usamii contain lower EtOH and higher acetic acid than media saccharified by A. shirousamii (P0.05). It is noteworthy that A. usamii could hydrolyze starch and protein in rice flour to prevent nutrient exhaustion during acetic acid production by A. pasteurianus. While nutrient exhaustion in media saccharified by A. shirousamii leads to the utilization of acetic acid known as over-oxidation.